Relação entre a complexidade estrutural de macrófitas e os atributos da assembleia de peixes em um reservatório Neotropical. - Dal Vesco, Bianca Morelatto (2022)
Habitat complexity is one of the main factors determining biological diversity and its assessment is a challenge that involves several variables. Submerged macrophytes are responsible for changes in habitat complexity and may enhance habitat conditions for different species. These plants usually colonize natural and artificial lentic environments, such as reservoirs, which have abiotic characteristics favorable to their establishment. The construction of the Itaipu Dam and the filling of the reservoir favored the establishment of macrophytes due to changes in flow dynamics. Therefore, the aim of this work was to evaluate whether habitat complexity, provided by macrophytes, is associated with changes in fish assemblage attributes (abundance, richness, and evenness) and composition. Linear regression models were applied to test the relationship between abundance, richness, and evenness with habitat complexity (expressed as macrophyte density - g/m²). In addition, Principal Coordinates Analysis (PCoA) and Spearman correlations were used to assess changes in the composition of fish assemblages according to macrophytes density. The results indicate a direct relationship between habitat complexity and fish assemblage attributes as well as associations between macrophyte density and fish assemblage composition, improving the knowledge about species preference for different levels of complexity. Thus, it is important to consider the behavior of species known to cause economic and ecological issues for future management and conservation efforts.